Scholarly Addiction: Doctor Faustus and the Drama of Devotion. (20th November 2016) - Lemon, Rebecca
Abstract: When The English Faust Book describes Faustus as addicted to study and Marlowe's Doctor Faustus depicts necromantic books as "ravishing, " these texts draw on classical and Renaissance notions of laudable addiction. Following its Latin origin in contract law, addiction appears in sixteenth-century writings as service, dedication, and devotion. Tracing invocations of addiction from Cicero to Perkins, this essay explores the influence of Calvin and Calvinist-minded Cambridge divines through Doctor Faustus's preoccupation with the challenge of addicted commitment. If Calvinists praise committed devotion, Marlowe challenges such views by staging the terror as well as the wonder of addictive release.